Connective tissue diseases an atlas of investigation and management - Gordon, Caroline, 1956-; Gross, Wolfgang L. (Atlas: Connective Tissue Diseases., 2011)
An illustrated guide to the investigation, diagnosis and management of connective tissue disorders. Overview of the general principles of assessment, the main focus is on specific inflammatory diseases affecting the connective tissues. Suitable for rheumatologists, general physicians, hospital pharmacists, doctors in training.